(untitled) (Global Journal of Computer Science and Technology, 2023)
Smart contracts are automated agreements in which the conditions between the purchaser and the vendor are encoded directly into lines of code allowing them to execute automatically Smart contracts have emerged as a ground-breaking technology facilitating the decentralized and trustless execution of agreements on blockchain platforms However the widespread adoption of smart contracts exposes them to various security threats leading to substantial financial losses and reputational harm Artificial Intelligence has the capability to aid in the detection and reduction of vulnerabilities thereby enhancing the overall strength and resilience of smart contracts This integration can create highly secure and transparent systems that reduce the risk of fraud corruption and other malicious activities thereby increasing trust and confidence in these systems and improving overall security This research paper delves into the innovative applications of Artificial Intelligence techniques to enhance the security of smart contracts Investigating the potential of AI in detecting vulnerabilities identifying potential attacks and offering automated solutions for safer smart contracts will significantly contribute to the development and flawless execution of this emerging technology